Penerapan Metode Game Devlopment Life Cycle (GDLC) pada Pengembangan Game Motif Batik Khas Yogyakarta - Renna Yanwastika Ariyana; Erma Susanti; Muhammad Rizqy Ath-Thaariq; Riki Apriadi (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Batik art is one of the arts of the Indonesian nation which continues to grow and develop today. Batik is a cultural heritage that must be preserved so that it is not claimed by foreign nations as its cultural heritage. Batik is often identified as something that is less attractive because it is considered old-fashioned and does not keep up with the times, causing almost a decade since the establishment of batik as a national culture, many do not know about it. Many people are trapped in the confusion of distinguishing batik from printed textile fabrics with batik motifs. Providing knowledge about batik from the age of children through the media of games is certainly the right thing to introduce and add insight to the art of Indonesian batik. In this research, a game will be developed to introduce batik motifs, especially batik motifs typical of Yogyakarta using the Game Development Life Cycle (GDLC) method where in this method there are 6 stages of development carried out which include the initialization stage, the pre-production stage, the production stage, the testing stage. alpha, beta release and release version. The developed game application can later be used to introduce batik to children. Through the game that was built, it is hoped that it can increase appreciation for the art of batik, in order to raise awareness and love for batik by fulfilling knowledge about batik.